Constant Observation Practices for Hospitalized Persons With Dementia: A Survey Study. Issue 4 (June 2019) - Sinvani, Liron; Strunk, Andrew; Patel, Vidhi; Shah, Shalin; Mulvany, Colm; Kozikowski, Andrzej; Boltz, Marie; Pekmezaris, Renee; Wolf-Klein, Gisele
Despite substantial staffing and cost implications, the use of constant observation (CO) has been poorly described in the acute care setting. The purpose of this cross-sectional, multicenter, survey study was to assess hospital provider practices regarding the use of CO. Of the 543 surveys distributed, 231 were completed across 5 sites. Most respondents worked on medical units (67.5%), as nurses (49.1%); 44.8% were white; and 75.6% were female. The majority (84.2%) reported at least 1 patient/wk requiring CO. Most frequent indication for CO was dementia with agitation (60.7%), in patients older than 70 (62.3%) and predominantly by nurse assistants (93.9%). Almost half (47.3%) stated they felt pressured to discontinue CO, despite a strong perceived benefit (76%). Enhanced observation (92.6%) was most frequently used to decrease CO. Finally, 77.9% perceived that those performing CO lacked training. Our study highlights the widespread use of CO for hospitalized older adults with dementia.